PEMANFAATAN ZAT WARNA ALAM DARI EKSTRAK KULIT AKAR MENGKUDU (Morinda citrifolia Linn) PADA KAIN KATUN - Thomas, Mariance; Manurung, Manuntun; Raka Astiti Asih, I. A. (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 2 Juli 2013, 2013)
The research about utilization of natural dyes from root bark extract of Morinda citrifolia on cotton fabric has been done. The extraction of root bark morinda was done by using water and methanol as solvent with ratio of 1:20 (w/v) (10 g sample : 200 mL solvent). The extract obtained from water was blackish brown, while from methanol solvent was reddish brown. The extract obtained was used to dye cotton fabric with addition of 1.00 g whiting as a mordant. Extracts of both solvents can dye cotton fabrics with varied colors : yellow, red, and red purple. Mordant can strengthen the bond between the fiber and dyes and sharpen the fabric color. Endurance test by using 0.5% detergent water to soak for 15 minutes, showing the colour of fabric without mordant easily fade, whereas the colour with mordant of whiting do not easily fade .
Keywords: Morinda citrifolia , extraction, cotton fabric, whiting, mordant